2020
DOI: 10.1039/d0ra07160a
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic quasi-one-dimensional layered transition-metal trichalcogenides: synthesis, properties and applications

Abstract: The strong in-plane anisotropy and quasi-1D electronic structures of transition-metal trichalcogenides (MX3; M = group IV or V transition metal; X = S, Se, or Te) have pronounced influence on moulding the properties of MX3 materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 169 publications
(301 reference statements)
0
46
0
Order By: Relevance
“…That the relation between electronic anisotropy and structure is unusual is also shown by the observation that the long axis of exfoliated CrSBr multilayers (which are platelets having one of their sides much longer than the other) corresponds to the crystallographic a-direction, that is, to the direction with low electrical conductivity. This is indeed rather unique, as it is commonly the case that materials exhibiting strongly anisotropic electronic transport are needles whose long axis points in the high conductivity direction (see, for examples, conductors such as ReS 2 , NbSe 3 , TiS 3 , ZrTe 5 , black phosphorus, or high-mobility organic semiconductors such as rubrene [31][32][33][34][35][36][37][38][39] ).…”
Section: Resultsmentioning
confidence: 99%
“…That the relation between electronic anisotropy and structure is unusual is also shown by the observation that the long axis of exfoliated CrSBr multilayers (which are platelets having one of their sides much longer than the other) corresponds to the crystallographic a-direction, that is, to the direction with low electrical conductivity. This is indeed rather unique, as it is commonly the case that materials exhibiting strongly anisotropic electronic transport are needles whose long axis points in the high conductivity direction (see, for examples, conductors such as ReS 2 , NbSe 3 , TiS 3 , ZrTe 5 , black phosphorus, or high-mobility organic semiconductors such as rubrene [31][32][33][34][35][36][37][38][39] ).…”
Section: Resultsmentioning
confidence: 99%
“…1 Very recently, it has been shown that they may also provide useful platforms for next-generation electronic and optoelectronic 2D materials. 2,3 The CDW material NbSe 3 for instance is one of the archetypal systems in low-dimensional materials science. 4,5 It was the first inorganic solid found to exhibit Froḧlich-type conductivity, and this observation launched a huge and continued interest on it.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Layered group V transition-metal trichalcogenides display a plethora of challenging physical and chemical properties such as charge density waves (CDW), superconductivity, easy chemical intercalation, and so forth . Very recently, it has been shown that they may also provide useful platforms for next-generation electronic and optoelectronic 2D materials. , The CDW material NbSe 3 for instance is one of the archetypal systems in low-dimensional materials science. , It was the first inorganic solid found to exhibit Fröhlich-type conductivity, and this observation launched a huge and continued interest on it. Almost 40 years later, very fundamental aspects of its physical and chemical behavior still remain challenging. NbSe 3 , is a room-temperature quasi-one-dimensional metal which undergoes two successive Fermi surface-driven incommensurate CDW transitions at 145 and 59 K, respectively. ,, After the second CDW transition, NbSe 3 still exhibits metallic character so that the Fermi surface is not completely removed by the CDWs.…”
Section: Introductionmentioning
confidence: 99%
“…That the relation between electronic anisotropy and structure is unusual is also shown by the observation that the long axis of exfoliated CrSBr multilayers (which are platelets having one of their sides much longer than the other) corresponds to the crystallographic a-direction, i.e., to the direction with low electrical conductivity. This is indeed rather unique, as it is commonly the case that materials exhibiting strongly anisotropic electronic transport are needles whose long axis points in the high conductivity direction TiS 3 , ZrTe 5 , black phosphorus or high-mobility organic semiconductors such as rubrene [31][32][33][34][35][36][37][38][39]).…”
Section: Resultsmentioning
confidence: 99%